Revolusi Media Pembelajaran Transformasi dari Tradisional ke Digital dalam Pendidikan di Medan - Santiya, Layla; Daulay, Tuti Alawiyah (Lembaga Yasin AlSys, 2025)
This study examines the transformation of instructional media from traditional to digital methods as an important phenomenon in education in line with the increasing use of technology in learning processes. It aims to analyze the shift from traditional to digital learning media and to evaluate its impact on student engagement and learning outcomes at the lower secondary school level. The study employed a mixed-methods approach with an exploratory case study design at a junior high school in Medan, involving 50 students and 15 teachers selected through purposive sampling. Quantitative data were collected using structured questionnaires and analyzed through linear regression, while qualitative data were obtained via semi-structured interviews and analyzed using thematic analysis. The findings indicate that 85% of students were more engaged in digital learning than in traditional learning, with an average test score increase of 25%, and 80% of students reported being more motivated to learn through the use of digital media. However, approximately 15% of students experienced difficulties in accessing the internet, which negatively affected their motivation and learning engagement. These results suggest that although digital media make a positive contribution to student learning outcomes, the success of their implementation is strongly influenced by the availability and quality of supporting infrastructure. The study underscores the importance of a balanced integration between traditional and digital learning media to enhance instructional effectiveness in the digital era.